Genomic Characteristics and Pan-Genome Analysis of Rhodococcus equi - Song, Yang; Xu, Xinmin; Huang, Zhenzhou; Xiao, Yue; Yu, Keyi; Jiang, Mengnan; Yin, Shangqi; Zheng, Mei; Meng, Huan; Han, Ying; Wang, Yajie; Wang, Duochun; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Rhodococcus equi is a zoonotic pathogen that can cause fatal disease in patients who are immunocompromised. At present, the epidemiology and pathogenic mechanisms of R. equi infection are not clear. This study characterized the genomes of 53 R. equi strains from different sources. Pan-genome analysis showed that all R. equi strains contained 11481 pan genes, including 3690 core genes and 602 ~ 1079 accessory genes. Functional annotation of pan genome focused on the genes related to basic lifestyle, such as the storage and expression of metabolic and genetic information. Phylogenetic analysis based on pan-genome showed that the R. equi strains were clustered into six clades, which was not directly related to the isolation location and host source. Also, a total of 84 virulence genes were predicted in 53 R. equi strains. These virulence factors can be divided into 20 categories related to substance metabolism, secreted protein and immune escape. Meanwhile, six antibiotic resistance genes (RbpA, tetA (33), erm(46), sul1, qacEdelta 1 and aadA9) were detected, and all strains carried RbpA related to rifamycin resistance. In addition, 28 plasmids were found in the 53 R. equi strains, belonging to Type-A (n = 14), Type-B (n = 8) and Type-N (n = 6), respectively. The genetic structures of the same type of plasmid were highly similar. In conclusion, R. equi strains show different genomic characteristics, virulence-related genes, potential drug resistance and virulence plasmid structures, which may be conducive to the evolution of its pathogenesis.